(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The purpose of this study was to test and analyze how financial literacy, materialism, and Allowance influence the saving decisions of Generation Z and consumptive behavior of Generation Z. This study uses quantitative research methods and focuses on the population of Generation Z in the provinces of West Java and Central Java, which includes a total of 21,989,129 individuals. 104 people were used in the study sample aged between 17 and 25 years. The data collection method consisted of distributing questionnaires with a 5-point Likert scale which was then analyzed using SEM through the use of the SmartPLS 3.2.9 application. Research findings show that financial literacy can positively affect Generation Z’s saving decisions, materialism can positively influence Generation Z’s saving decisions, and Allowance can positively influence Generation Z’s saving decisions. Conversely, financial literacy can negatively affect Generation Z’s consumptive behavior, materialism can positively affect Generation Z’s consumptive behavior, and Allowance does not affect the consumptive behavior of Generation Z.